Health Literacy as the Foundation of Nursing Education in the Era of Digital Transformation - Hardjito S. Darmojo; Partono Siswosuharjo; M. Adila Rossa (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
Digital transformation has significantly changed the way health information is accessed, understood, and utilized, thus requiring nursing staff to have adequate digital health literacy competencies. Health literacy is no longer limited to the ability to understand conventional health information, but also includes critical skills in navigating and evaluating digital-based health information sources. This study aims to analyze the role of health literacy as a foundation in developing digital health literacy in nursing students in the era of digital transformation. The study used a quantitative design with a descriptive-correlation survey approach. The sample consisted of 200 nursing students selected through stratified random sampling. Data were collected using the Health Literacy Questionnaire (HLQ) and the eHealth Literacy Scale (eHEALS), then analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results showed that the level of health literacy and digital health literacy of students was in the moderate to high category. There was a significant positive relationship between general health literacy and digital health literacy (r = 0.53; p < .001). The regression analysis showed that general health literacy was the main predictor of digital health literacy, followed by technology-based learning experiences. However, the ability to evaluate the credibility of digital health information remains the lowest. This finding underscores the importance of systematically integrating digital health literacy into the nursing education curriculum to equip students with critical, adaptive, and professional competencies to face the challenges of nursing practice in the digital era.